КОМПОНЕНТНА СТРУКТУРА МУЗИЧНОГО МИСЛЕННЯ ФАХІВЦІВ МИСТЕЦЬКОГО ПРОФІЛЮ - Гусак, Владислав; Шевченко, Роман (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті викладена сутність понять «мислення» і «музичне мислення». На основі ретроспективного аналізу сучасної наукової літератури висвітлені різноманітні фактори виявлення, сфери реалізації і підходи щодо характеристики компонентної структури дефініції «музичне мислення». Автор досліджує специфіку активізації психомоторного компоненту як різновиду наочно-дійового мислення в ієрархічній структурі музичного мислення фахівців мистецького профілю у процесі інструментальної підготовки. В статье изложена сущность понятий «мышление» и «музыкальное мышление». На основе ретроспективного анализа современной научной литературы освещены разнообразные факторы проявления, сферы реализации и подходы до характеристики компонентной структуры дефиниции «музыкальное мышление». Автор исследует специфику активизации психомоторного компонента как разновидность наглядно-действенного мышления в иерархичной структуре музыкального мышления специалистов художественного профиля в процессе инструментальной подготовки. The article proposes the essence of terms «comprehension» and «music comprehension». On the basis of retrospective analysis of modern scientific literature different factors of revealing, sphere of realization and approaches toward characterizing the componential structure of the term «music comprehension» were enlighten. The author investigates peculiarities of development of psycho motility component as a subtype of visual comprehension in the hierarchical structure of music comprehension of teachers in the process of musical training. As psychological process of sensual comprehension, representing and realizing of music images, music comprehension is naturally connected with instrumental musical performance, has active creative character, differs by individual peculiarities – independent and critical features, usage of complex polymodal dynamic emotional and audio-motor comprehension, images and senses. Psycho-motor component of music comprehension provides unity of performance with music thought, artistic image, and emotional feelings and reflects in the closed circle of psycho motility actions «sound purpose – performance – control».